Gambaran Masa Pemulihan Sistem Kardiovaskular Berdasarkan Indeks Masa Tubuh Pada Mahasiswa Fakultas Kedokteran Universitas Gunadarma - Zulyani, Febriyanti; Millenia, Fadya; Suhartini, Srimukti; Ningsih, Sri Rahayu (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Physical activity encompasses all body movements carried out for work, play, or travel, while physical inactivity is characterized byminimal movement and low energy expenditure. Body Mass Index (BMI) and recovery heart rate are important indicators in assessingfitness levels and health risks. This study aims to determine whether there are differences in cardiovascular recovery time after physicalactivity based on BMI categories among medical students at Gunadarma University. The study employs a cross-sectional design with purposive sampling among FKUG students who meet the inclusion criteria. Data were analyzed using paired T-tests and One WayANOVA according to data distribution. The procedure consists of two stages: measuring blood pressure, heart rate, O₂ saturation, and BMI before and after a six-minute walk test, followed by measuring heart rate recovery time after approximately 20 minutes of rest. Most respondents were female (92.5%) from the 2019 cohort (77.4%), with an average age of 20.79 years. A significant increase was observedin systolic blood pressure and heart rate after training (p=0.001), but not in diastolic pressure (p=0.622). No significant difference wasfound in recovery time based on BMI category (p=0.516). Physical training significantly affected certain physiological parameters such as systolic pressure and heart rate, but BMI status did not significantly contribute to post-activity recovery speed.  Keywords:     Physical Activity, Body Mass Index, Medical Students, Cardiovascular Recovery,  Pulse Rate